Users Experience Analysis of the Zoom Meeting Application - Wijaya Laksana, Gusti Bagus; Candiasa, I Made; Dantes, Gede Rasben (Politeknik Ganesha Medan, 2023)
This research aimed to analyze the User Experience analysis of the Zoom Meeting application according to the perspectives of lecturers and students during online learning in the new normal era because the Zoom application is considered to have numerous outstanding features. The population in this research were 2 lecturers and 123 students of the Bachelor of Elementary School Teacher Education Study Program in the 2021/2022 academic year in Bali. The purposive sampling technique was used along with the questionnaire and in-depth interview. As a result, the attractiveness, clarity, efficiency, and stimulation aspects scale got the average positive result from the questionnaire because the value obtained was more than 0.8. Furthermore, the average questionnaire scale was neutral for the accuracy and novelty aspects because the values obtained were from -0.8 to 0.8. Therefore, the accuracy aspect has the lowest value compared to other aspects. It was also verified from the data obtained from the in-depth interview results, which showed various problems and obstacles experienced by users in terms of the accuracy of the Zoom Meeting application when used as an online learning medium, i.e., difficulties in conducting disciplinary assessments and conducting lectures that required practical skills. Although Zoom has many benefits for online learning, it still has several limitations that must be addressed by lecturers, students, and Zoom developers.